Investigation of the effect of allithiamine-enriched feed on the poultry gut microbiome composition and resistome - Szőke, Zsombor; Péter Dávid; Péter Fauszt; Emese Szilágyi-Tolnai; Endre Szilágyi; Anna Szilágyi-Rácz; László Stündl; Ferenc Gál; Judit Remenyik; Melinda Paholcsek (Acta Agraria Debreceniensis, 2023)
Over the past 20–25 years, the poultry industry has evolved into a specific protein production system. However, the stress resulting from intensive rearing practices has led to numerous negative consequences, making the optimisation of livestock gut microbiome composition crucial for mitigating these effects. Advancements in modern molecular biology methods have brought attention to the impacts of nutrients on gut microbiota. In our study, we extensively investigated the changes induced by feed formulations rich in phytonutrients on the gastrointestinal microbiota of livestock using targeted 16S rRNA amplicon sequencing. Our objective is to examine how the developed feed prototype affects the composition of core microbiomes in raised poultry, community diversity, and the resilience of complex microbial networks. We seek correlations between biological livestock and environmental samples to identify which community constituents, in what proportions and occurrences, may play a role in the development of specific diseases. Based on our measurement results, it can be asserted that allithiamine positively modulated "beneficial" community constituents. Beyond the impact of allithiamine-enriched feed rich in phytonutrients, the composition of the microbial community in the poultry gastrointestinal tract is significantly influenced by the age of the birds. Furthermore, due to the presence of multi-drug-resistant pathogens in environmental samples from livestock facilities, appropriate transmission risk management measures are of paramount importance.